Electronic or automated sphygmomanometers (ANSI/AAMI, 1992)
This stand establishes labeling requirements, safety and performace requirements, and referee test methods for electronic or automated sphygmomanometers used in the indirect measurement of blood pressure. Specific requirements for ambulatory blood pressure monitors are included.